The effect of humor events on workers’ well-being: the moderating role of gelotophobia - Junça Silva, A.; Caetano, António; Lopes, M. (15th Conference of the International Society for Quality of Life Studies (ISQOLS): Quality of Life: Towards a Better Society., 2017)
Purpose Gelotophobia is a subclinical form of social anxiety. It has been defined as the fear of being laughed at and implies differences in humor reception. Every day, employees have to face diverse (positive and negative) humorous events. These events tend to arouse positive and negative affective reactions. The role of gelotophobia at work has been neglected, thus, we intend to analyze the role of gelotophobia on the relationship between humor events, affect and employees’ well-being. Methodology We used a quasi-experimental study (2x2: high vs. low gelotophobia x recall of positive humor event vs. negative humor event) and we asked participants to recall humor episodes that have occurred in organizational context. Results Results showed that gelotophobia moderates the relationship between humor events and affect, and this acts as a mediator of the relationship between humor events and well-being. Limitations The sample size raises some concerns regarding the generalization of the data. The use of recalled events may have some memory bias. Research/Practical implications This research sheds light on the role that gelotophobia may play in inhibiting positive affect and enhancing negative affect prompted by humor events. Managers may find it useful to better manage their employees’ emotions. Originality/Value This is the first study to examine gelotophobia as a buffer of the relationship between humor daily events and well-being at work.